A New Architecture for Fibrous Organic Transistors Based on a Double‐Stranded Assembly of Electrode Microfibers for Electronic Textile Applications. Issue 23 (12th April 2019) - Kim, Soo Jin; Kim, Hyoungjun; Ahn, Jongtae; Hwang, Do Kyung; Ju, Hyunsu; Park, Min‐Chul; Yang, Hoichang; Kim, Se Hyun; Jang, Ho Won; Lim, Jung Ah
Abstract: Herein, a unique device architecture is proposed for fibrous organic transistors based on a double‐stranded assembly of electrode microfibers for electronic textile applications. A key feature of this work is that the semiconductor channel of the fiber transistor comprises a twist assembly of the source and drain electrode microfibers that are coated by an organic semiconductor. This architecture not only allows the channel dimension of the device to be readily controlled by varying the thickness of the semiconductor layer and the twisted length of the two electrode microfibers, but also passivates the device without affecting interconnections with other electrical components. It is found that the control of crystalline nanostructure of the semiconductor layer is critical for improving both the production yield of the device and the charge‐carrier transport in the device. The resulting fibrous organic transistors show a high output current of over −5 mA at a low operation voltage of −1.3 V and a good on/off current ratio of 10 5 . The device performance is maintained after repeated bending deformation and washing with a strong detergent solution. Application of the fibrous organic transistors to switch current‐driven LED devices and detection of electrocardiography signals from a human body are demonstrated. Abstract : Fibrous organic transistors with a double‐stranded assembly of electrode microfibers are successfully demonstrated. This architecture not only allows the channel dimension of the device to be readily controlled by varying the thickness of the semiconductor layer and the twisted length of the two electrode microfibers, but also passivates the device without affecting interconnections with other electrical components.